2015
DOI: 10.1002/hup.2511
|View full text |Cite
|
Sign up to set email alerts
|

Acute personalized habitual caffeine doses improve attention and have selective effects when considering the fractionation of executive functions

Abstract: Caffeine is widely used, often consumed with food, and improves simple and complex/executive attention under fasting conditions. We investigated whether these cognitive effects are observed when personalized habitual doses of caffeine are ingested by caffeine consumers, whether they are influenced by nutriments and if various executive domains are susceptible to improvement. This was a double-blind, placebo-controlled study including 60 young, healthy, rested males randomly assigned to one of four treatments: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 79 publications
3
36
0
Order By: Relevance
“…Another finding of the present study was that a single instance of caffeine intake significantly shortened the response time in the Harsh-braking test, which is consistent with the finding that caffeine increases mental arousal[ 27 ]. A driver’s recognition and error in judgment are factors associated with a traffic accident.…”
Section: Discussionsupporting
confidence: 90%
“…Another finding of the present study was that a single instance of caffeine intake significantly shortened the response time in the Harsh-braking test, which is consistent with the finding that caffeine increases mental arousal[ 27 ]. A driver’s recognition and error in judgment are factors associated with a traffic accident.…”
Section: Discussionsupporting
confidence: 90%
“…Also, these results are consistent with the results of some other studies [5,9,15], that showed caffeine can improve the brain's executive functions. In addition, these results are in line with the result of Lanini et al study, which shows that caffeine causes an increase in information processing speed [7]. So consuming a cup of coffee before studying is recommended.…”
Section: Discussionsupporting
confidence: 81%
“…Caffeine consumption can also promote the cognitive and executive functions of the human brain [5]. An increase in selective attention and information processing speed has also been reported after drinking beverages containing caffeine [7,14]. The effectiveness of caffeine on cognitive functions was also observed using MRI [8,15].…”
Section: Introductionmentioning
confidence: 96%
“…It showed that consuming 200 mg of caffeine alone can significantly and consistently improve the number of correct responses while decreasing the reaction time to stimuli compared to placebo over two hours of testing. Meanwhile, Lanini et al [164] reported that personalized individual caffeine dosages from 25 mg to 300 mg improved the vigilance of 60 young adults who performed psychomotor vigilance task. In this study, caffeine has significantly reduced the mean reaction time and led to less variable response times from the beginning until the end of a 10-minute performance of vigilance task.…”
Section: Vigilance Enhancement Based On Conventional Techniquesmentioning
confidence: 99%
“…The highest improvements (more than +15%) on monotonous vigilance tasks were reported when video game and transcranial direct current stimulations were used [32,33,49,52]. Haptic stimulation (HPS), modafinil, cognitive work-modulation (CWM), tACS, chewing gum (CG), and caffeine [28,29,35,38,46,164,206] showed an improvements of more than +%10. However, music, binaural beats (BBs), and fragrance produced improvements of equal or less than +10% in the simple monotonous vigilant tasks [41,123,124,125,193].…”
Section: Comprehensive Summarymentioning
confidence: 99%